Early Modern Spaces in Motion Design, Experience and Rhetoric - Anderson, Jocelyn; Bensoussan, Nicole; Campbell, James W. P.; Jakovac, Gašper; Schmidt, Freek; Skelton, Kimberley; Skelton, Kimberley; Thomas, Edmund (Amsterdam University Press, 2021)
Stretching back to antiquity, motion had been a key means of designing and describing the physical environment. But during the sixteenth through eighteenth centuries, individuals across Europe increasingly designed, experienced, and described a new world of motion: one characterized by continuous, rather than segmented, movement. New spaces that included vistas along house interiors and uninterrupted library reading rooms offered open expanses for shaping sequences of social behaviour, scientists observed how the Earth rotated around the sun, and philosophers attributed emotions to neural vibrations in the human brain. Early Modern Spaces in Motion examines this increased emphasis on motion with eight essays encompassing a geographical span of Portugal to German-speaking lands and a disciplinary range from architectural history to English. It consequently merges longstanding strands of analysis considering people in motion and buildings in motion to explore the cultural historical attitudes underpinning the varied impacts of motion in early modern Europe
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: Art and Material Culture; Early Modern Period; History; ARCHITECTURE / History / Renaissance; Architecture and society -- Europe -- History -- 16th century; Architecture and society -- Europe -- History -- 17th century; Architecture and society -- Europe -- History -- 18th century; Architecture -- Europe -- History -- 16th century; Architecture -- Europe -- History -- 17th century; Architecture -- Europe -- History -- 18th century; Motion in architecture